Lanthanide doped coordination polymers with tunable afterglow based on phosphorescence energy transfer - Yang, Yongsheng; Wang, Ke-Zhi; Yan, Dongpeng (Chemical communications (Cambridge, England), 2017)
Lanthanide ion doped coordination polymers (CPs) exhibit an unusual red/green afterglow with long photoemission lifetimes (10.54 ms for Eu 3+ and 57.66 ms for Tb 3+ ) due to the phosphorescence energy transfer at room temperature.